Antiplatelet Effects of Qishen Yiqi Dropping Pill in Platelets Aggregation in Hyperlipidemic Rabbits - Yi Wang (Evidence-Based Complementary and Alternative Medicine, 2012)
We investigated the effects of Qishen Yiqi Dropping Pill (QSYQ) on platelets aggregation and its possible mechanisms. Hyperlipidemic model in rabbits was produced by a high fat/cholesterol diet for 6 weeks, the therapeutic effect of QSYQ with 2.0 g/kg, 1.0 g/kg, and 0.5 g/kg was observed. Fourteen days after drug treatment, platelet aggregation induced by adenosine diphosphate (ADP), arachidonic acid (AA), and collagen (COLL) was significantly reduced in rabbits of model group. Moreover, β-thromboglobulin (β-TG) level decreased obviously but no significant change in P-selectin and platelet factor 4 (PF4) level, while QSYQ significantly decreased the ratio of thromboxane B2 (TXB2) to 6-keto-prostaglandin F1α (6-Keto-PGF1α) and increased cyclic adenosine monophosphate (cAMP) level in rabbits. In summary, QSYQ can improve platelets aggregation and inhibit the over-release of β-TG in hyperlipidemic rabbits; and the increased cAMP level may be involved in this process. These results suggest that the antiplatelet aggregation effect of QSYQ may be due to its ability to increase cAMP level for improving cAMP metabolism.